TRANSFORMING PUBLIC ORGANIZATION CULTURE TOWARDS MORE RESPONSIVE SERVICES: Transformasi Budaya Organisasi Publik Menuju Pelayanan yang Lebih Responsif - Hendri Gunawan; Aldri Frinaldi; Angga Putra Tri Rezeki (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
The transformation of public organizational culture has become a strategic issue in improving the responsiveness of public services amid increasingly complex and dynamic societal demands. This study aims to systematically examine the role of public organizational culture transformation in fostering more responsive, adaptive, and accountable public services. The research employed a Systematic Literature Review (SLR) of scholarly articles published between 2020 and 2025, sourced from Google Scholar. Data were analyzed using a content analysis approach to identify key themes and patterns across the literature. The findings indicate that public service responsiveness is shaped by civil servant professionalism, adaptive leadership, service innovation and digitalization, institutional change, and consistent regulatory and governance support. Organizational culture transformation extends beyond technological adoption to encompass changes in values, work ethics, and service orientation. This study concludes that transforming public organizational culture is a fundamental prerequisite for achieving public services that are citizen-oriented, transparent, and sustainable.